Bilayer skyrmion dynamics on a magnetic anisotropy gradient - Ang, Calvin Ching Ian (2019)
Magnetic skyrmion transport has been primarily based on the use of spin torques which require high current densities and face performance deterioration associated with Joule heating. In this work, we derive an analytical model for energy efficient skyrmion propagation in an antiferromagnetically-coupled bilayer structure using a magnetic anisotropy gradient. The interlayer skyrmion coupling provides a strong restoring force between the skyrmions, which not only prevents annihilation but also increases their forward velocity up to the order of km s–1. For materials with low Gilbert damping parameter, the interlayer skyrmion coupling force can be amplified up to ten times, with a corresponding increase in velocity. Furthermore, the analytical model also provides insights into the dynamics of skyrmion pinning and relaxation of asymmetric skyrmion pairs in bilayer-coupled skyrmion systems.